NAQÍL-MAQALLARDÍŃ TIPOLOGIYASÍ - Qazaxbaev, S. (SCIENCE and SOCIETY, 2024)
The socio-cultural aspects of proverbs and their reflection of folk culture are analyzed in the work. Effective ways of learning a foreign language are described based on the comparative analysis of articles in different languages.